1998
DOI: 10.1542/peds.102.5.1148
|View full text |Cite
|
Sign up to set email alerts
|

Early Developmental Outcome After the Norwood Procedure for Hypoplastic Left Heart Syndrome

Abstract: Children with HLHS most often function in the low-normal range of intelligence and adaptive behavior. A prolonged circulatory arrest time may result in decreased intellectual function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
75
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(76 citation statements)
references
References 20 publications
1
75
0
Order By: Relevance
“…As in other reports, 29,32 the diagnosis of HLHS was a risk factor for poor outcome in this series; however, the number of patients was exceedingly small (nϭ5), and the effects of diagnosis were confounded by use of circulatory arrest in this group. Kern and colleagues 33 reported a negative correlation between the duration of circulatory arrest during stage I reconstruction (mean, 56 minutes) and full-scale IQ. In our series, these patients represent an early portion of the learning curve with surgical management of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…As in other reports, 29,32 the diagnosis of HLHS was a risk factor for poor outcome in this series; however, the number of patients was exceedingly small (nϭ5), and the effects of diagnosis were confounded by use of circulatory arrest in this group. Kern and colleagues 33 reported a negative correlation between the duration of circulatory arrest during stage I reconstruction (mean, 56 minutes) and full-scale IQ. In our series, these patients represent an early portion of the learning curve with surgical management of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39][40] One study showed the duration of DHCA to be inversely associated with performance IQ in a small cohort of 14 patients. 39 For children after Norwood MBTS surgery, a strong correlation has been found between the MDI at 18 to 24 months of age and full-scale intelligence scores at 5 years of age. 41 In the present study cohort, MDI scores and the incidence of mental delay did not improve in the recent surgical era.…”
Section: Mental and Psychomotor Outcomesmentioning
confidence: 99%
“…Sixty-four per cent of these infants had varying degrees of mental retardation and 73% had substantial functional disability. However, Kern et al (44) noted that in their cohort, the median full scale IQ was 88 and only 8.3% of their patients met the diagnostic criteria for mental retardation. They found that although the results were not statistically significant, all HLHS patients scored lower on average on neurodevelopmental tests compared with matched controls (44).…”
Section: Surgical Treatment and Their Outcomesmentioning
confidence: 85%
“…However, Kern et al (44) noted that in their cohort, the median full scale IQ was 88 and only 8.3% of their patients met the diagnostic criteria for mental retardation. They found that although the results were not statistically significant, all HLHS patients scored lower on average on neurodevelopmental tests compared with matched controls (44). The cause of a high prevalence of developmental disabilities remains unclear, illustrating the need to evaluate these patients continuously to assess their quality of life (2,17).…”
Section: Surgical Treatment and Their Outcomesmentioning
confidence: 85%